Seismic diffraction imaging in laterally varying velocity media for frequency bandwidth expansion - Application in carbonate field Sarawak, Malaysia - Bashir, Y. (Society of Petroleum Engineers, 2019)
Seismic Imaging for the small-scale feature in complex subsurface geology such as Carbonate is not easy to capture because of propagated wave affected by heterogeneous properties of objects in the subsurface. The principal goal of anisotropic seismic diffraction & reflection imaging is to get a subsurface image of structural features with the greatest sharpness or resolution. In this paper, we have presented a new approach for anisotropic diffraction preservation using offset and angle domain data during the initial data processing. Which leads to the better preservation of diffractions amplitude in laterally varying velocity condition. The plane-wave destruction filter is used with a modified approximation for Diffraction separation as the conventional filtering techniques mixed the diffraction amplitudes when there are a series of diffraction hyperbola. Further, the implementation of the proposed method has proven on carbonate field data from Sarawak Basin for steeply dipping Carbonate Build-up. Â© 2019, Society of Petroleum Engineers